Evaluation of The Suitability of High-Alert Medication Storage in the Pharmaceutical Warehouse of the Indonesian Red Cross (PMI) Bogor Hospital - Nyayu Siti Aminah Lily Elfrida; Alya Ramadhani Baladraf; Nisa Najwa Rokhmah (Jurnal Ners, 2025)
The storage of high-alert medications requires evaluation to prevent medication errors and inappropriate drug use and to facilitate the monitoring as well as control of these medications. Hospitals need to develop policies for managing high-alert medications. Therefore, the storage system must be established and aligned with actual conditions to ensure accurate drug delivery. This study aimed to describe the storage of high-alert medications in the pharmacy warehouse of PMI Bogor Hospital in 2023, determine the level of compliance with the storage of high-alert medications, assess the impact of storage practices on drug damage, and describe the knowledge and behavior of warehouse staff regarding high-alert medication storage. The results showed that the average compliance rates were as follows: 71% for Look-Alike Sound-Alike (LASA) medications (good), 73% for high-concentration electrolytes (good), 88% for narcotics (very good), 76% for psychotropics (good), and 75% for precursors (good). The staff's knowledge was rated as very good, with an average score of 9.17, while their behavior was rated as good, with a score of 9.5.